A Literature Review Leveraging Low-Cost MEMS Accelerometers and Raspberry Shake Sensors for Structural Health Monitoring and Seismic Applications - Yobel Eliezer Mahardika; Adhe Abdurrafi (Yayasan Kita Menulis - JoCPES, 2024)
A viable approach for real-time seismic and structural health monitoring (SHM) applications is the combination of inexpensive MEMS accelerometers with Raspberry Shake sensors. Building on recent developments in electrochemical seismometry and MEMS-based sensor technology, this study assesses the viability of employing these reasonably priced sensors to record seismic waves and structural vibrations, which are essential for determining the integrity of infrastructure and identifying early indicators of structural fatigue. While research on seismic applications emphasizes the requirement for easily accessible, large-scale deployment choices, literature on MEMS applications emphasizes improvements in sensitivity, frequency range, and cost-efficiency. In this investigation, a network of MEMS accelerometers and Raspberry Shake devices is deployed in different structural situations. Custom algorithms are used for data collection and processing. Results indicate that these MEMS-based systems offer adequate accuracy in frequency and amplitude response compared to traditional high-end seismic sensors, demonstrating significant potential in cost-sensitive environments. By leveraging these compact, economical sensors, this approach enables scalable and accessible monitoring solutions, supporting resilient infrastructure management and enhanced seismic hazard assessment.